Validation of ocular trauma score (OTS) in open- and closed-globe injuries in Indian patients - Fatema J Noble; Sumeet T Lahane; Tatyarao P Lahane; Ragini H Parekh; Sayalee T Lahane; Priyanka P Dhaytadak; Ashish K Jain (Indian Journal of Ophthalmology, 2025)
Purpose: To validate the predictive value of the ocular trauma score (OTS) in open- and closed-globe eye injuries in the Indian context. Design: Prospective interventional case series. Methods: This study, conducted at a tertiary healthcare institute from January 2018 to June 2019, included 150 eyes of 150 patients with open- and closed-globe injuries. Inclusion criteria were patients with globe injuries who provided informed consent and had complete OTS data. Exclusion criteria included electric, chemical, and thermal injuries, prior surgery, pre-existing poor visual acuity (VA), and severe systemic injuries. There was no randomization. Demographic details, initial and final VA, injury type, and OTS variables were recorded. Patients were classified into OTS categories preoperatively based on Kuhn et al.’s system, and VA distribution was compared with the original study. The main outcome was to assess the correlation between the final BCVA at 6 months post-intervention and the predicted VA based on the OTS category. Results: A total of 150 patients (72% open globe, 28% closed globe) were included, with a male-to-female ratio of 4.5:1. The mean age ± SD was 29.34 ± 17.49 years. OTS classification showed 6% in OTS 1, 17% in OTS 2, 67% in OTS 3, 4% in OTS 4, and 6% in OTS 5. Final VA was ≤20/40 (41%), 20/50–20/200 (20%), 20/200–1/200 (15%), HM/PL (15%), and NLP (9%). Final VA post-treatment correlated with predicted VA as per the OTS category (Spearman’s r = 0.53, P < 0.001). Conclusion: OTS provides reliable prognostic information and has fair predictive value for final VA in open- and closed-globe injuries.